2019
DOI: 10.1016/j.pbb.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the effect of bupropion and naltrexone combination on alcohol drinking in mice

Abstract: A fixed dose combination of bupropion (BPP) and naltrexone (NTX), Contrave®, is an FDA approved pharmacotherapy for the treatment of obesity. A recent study found that combining BPP with low-dose NTX reduced alcohol drinking in alcohol-preferring male rats. To explore potential pharmacological effects of the BPP+NTX combination on alcohol drinking, both male and female C57Bl/6J mice were tested on one-week drinking-in-the dark (DID) and three-week intermittent access (IA) models. Neuronal proopiomelanocortin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…To the best of our knowledge, the current study presents the first data showing that NTX reduces saccharin intake using a DID procedure. A combination of bupropion 10 mg/kg + NTX 1 mg/kg, capable of reducing 4% sucrose intake, did not affect 0.1% saccharin DID consumption (Zhou et al, 2019). However, previous research using non-DID procedures has found that opioid receptor antagonism can reduce saccharin intake (Lynch and Libby, 1983;Chow et al, 1997;Biggs and Myers, 1998).…”
Section: ! 12mentioning
confidence: 68%
See 3 more Smart Citations
“…To the best of our knowledge, the current study presents the first data showing that NTX reduces saccharin intake using a DID procedure. A combination of bupropion 10 mg/kg + NTX 1 mg/kg, capable of reducing 4% sucrose intake, did not affect 0.1% saccharin DID consumption (Zhou et al, 2019). However, previous research using non-DID procedures has found that opioid receptor antagonism can reduce saccharin intake (Lynch and Libby, 1983;Chow et al, 1997;Biggs and Myers, 1998).…”
Section: ! 12mentioning
confidence: 68%
“…NTX is known for its efficacy in reducing high alcohol drinking in relapsing patients (Volpicelli et al, 1992;Kiefer et al, 2003;Jonas et al, 2014). NTX, alone or in combination with other drugs, has been shown to reduce EtOH intake using DID methodology (Kamdar et al, 2007;Tarragón et al, 2012;Ripley et al, 2015;Zhou et al, 2019;Navarro et al, 2019). These results add to an extensive list of studies indicating that NTX reduces EtOH consumption using a variety of methodologies and animal models (Davidson and Amit, 1997;Sharpe and Samson 2001;Fachin-Scheit et al, 2006), including genetically predisposed EtOH-preferring strains of rodents such as B6 mice (Le et al, 1993, Phillips et al, 1997Middaugh et al, 2003;Dhaher et al, 2012).…”
Section: ! 12mentioning
confidence: 76%
See 2 more Smart Citations
“…For this reason, a comparison of 4 weeks MC model with 4 weeks LD diet potentially decreases the duration of alcohol exposure effect but increases more the differences between the amount of alcohol consumed by the mice in each model. Third of all, to increase the sensitivity of our analysis we used in our experiments only female mice as is pretty well known that the effect of alcohol is sex dependent in mice and humans 55,[60][61][62][63][64] . Actually, our ongoing current work in the lab is focused on specific cellular immune effects present only in females and not observed in male mice (data not presented, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%